Unemployment and the dynamics of offender populations - Collins, Mark F. (Journal of quantitative criminology, 1995)
This paper models the increase in the participation rate of criminal behavior as either the initiation rate or the career length of criminals changes in response to increases in unemployment. Even with large instantaneous increases in unemployment, the models show a very slow increase in the criminal participation rate, giving a possible explanation of the failure of many studies to demonstrate a link between unemployment and crime levels.